Perubahan Karakteristik Pengunjung Ruang Terbuka Hijau Perkotaan Sebagai Urban Tourism di Taman Alun-Alun Pacitan - Riswandha Risang Aji; Visilya Faniza (Universitas Diponegoro, Indonesia, 2021)
Tourism is a sector that is quite developed in Indonesia and in the world. Tourism has a multiplier effect that can develop other sectors that support the development of tourism itself. However, just like other sectors, the COVID-19 pandemic is affecting tourism. Many tourists spend their holidays at home because of the government's advice to stay at home. One type of tourism that is quite developed is Urban Tourism. One of Urban Tourism is urban green open space. The urban green open space which is the object of this research is the Taman Alun-Alun Pacitan. This study aims to describe the characteristics transformation of tourists or visitors and the role of Taman Alun-Alun Pacitan as a green open space in the pre-pandemic period and during the pandemic. The method used in this research is quantitative method using a questionnaire as a data collection tool and descriptive analysis to process the data. The results of this study show that the visitor of Taman Alun-Alun Pacitan characteristics have transformed from the pre-pandemic period and during the pandemic. The changes include the distance where visitors live, which narrows down to become residents who live nearby during the pandemic. The conclusion of this research is that Taman Alun-Alun Pacitan has changed its role from initially acting as a city level green open space in the pre-pandemic period, to becoming more dominant as a neighbourhood level green open space during the pandemic.